Prebavna mikrobiota kot dejavnik pri razvoju debelosti - Jerman, Vesna (Acta agriculturae Slovenica, 2010)
The increased prevalence of obesity in modern society is associated with incidence of obesity related diseases and represents a financial burden on public health. Important discovery in the field of microbial ecology of the gut was the possible involvement of the gut microbiota in obesity development. Using new molecular techniques and gnotobiotic animal models has revealed the relation between the regulation of body mass and energy balance of the host with the microbial community of the gut. Gut microbiota affects nutrient intake, facilitate the extraction of energy from food and promote storage of the calories in host adipose tissue through processes of fermentation, absorption and through the effect on the expression of host genes (e.g. Fiaf) and the activity of host enzymes (e.g. AMPK). In obese mice and humans the gut microbiota is clearly able to obtain energy from food more effectively as in the lean subjects. There are significant differences in the composition of microbial communities in relation to fat vs. lean phenotype. In the gut of obese animals and humans the increased proportion of the Firmicutes at the expense on Bacteroidetes was consistently detected. Both are the dominant bacterial groups in mammalian gastrointestinal tract, accounting together for 90% of all bacteria. It has been shown that gut microbiota is involved also in patophysiology of obesitz through factors such as microbial LPS. Existing results show that high fat diet can affect the composition of microbial community in the gut and that these changes can further affect the incidence of metabolic disease. This evidence potentially opens a new field of manipulation of the gut microbiota as a new strategy to treat obesity and related diseases.
Keywords: prebava; prebavila; prebavni trakt; mikrobiota; črevesna mikroflora; microbiology; mikrobiologija; debelost; genomika